An algorithm for annotation and classification of T. cruzi MASP sequences: towards a better understanding of the parasite genetic variability - Dean, Aldana Alexandra Cepeda; Berná, Luisa; Robello, Carlos; Buscaglia, Carlos Andrés; Balouz, Virginia (BMC genomics, 2025)
Background Trypanosoma cruzi , the protozoan causing Chagas disease, is responsible for a neglected tropical disease affecting millions in Latin America. Its genome contains rapidly evolving multigene families, such as mucins (TcMUC), trans-sialidases (TS), and mucin-associated surface proteins (MASP), which are essential for parasite transmission and disease mechanisms. However, methodological challenges in genome assembly and annotation have limited the characterization of these gene families, particularly MASPs. Results We developed a bioinformatic pipeline for the automatic identification, characterization, and annotation of MASPs directly from T. cruzi genome assemblies. This algorithm, based on a manually curated MASP database and HMM-based identification of MASP diagnostic motifs, enables the robust classification of these molecules into canonical MASPs, MASP-related molecules (mostly pseudogenes), and chimeric sequences combining MASPs and TcMUC/TS genes. Validation against a rigorously annotated dataset demonstrated high accuracy, and allowed us to reclassify misanotated sequences and, more crucially, to accurately identify previously unrecognized canonical MASPs and MASP chimeras. This algorithm was then used to explore the MASP repertoire in the genomes of 13 parasite strains from different evolutionary lineages, revealing patterns of diversity. For instance, TcI and TcII strains exhibited higher ratios of canonical MASP/MASP-related molecules and a greater abundance of MASP chimeras, suggesting that their genomes are under strong selective pressures towards maintaining a broader panel of full-length MASP genes at the expense of pseudogenes. On the contrary, structural features of canonical MASPs, MASP-related sequences, and MASP-chimeras were largely conserved across parasite genomes. Conclusions This novel pipeline automates the annotation of MASPs, a key surface protein family unique to T. cruzi , improving genome annotation and enabling robust comparative analyses. It provides an essential tool for exploring the evolutionary dynamics of multigene families in T. cruzi and could be extended to other gene families.